2021
DOI: 10.1109/tdei.2020.009101
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Pollution Flashover of a Slurry Coalescence Superhydrophobic Coating

Abstract: In this paper, the pollution flashover performance of a superhydrophobic surface with different coating strategies are studied. The results show that a superhydrophobic coating is effective in preventing pollution flashover under high voltage. The superhydrophobic coatings show increased pollution flashover voltage when compared to room temperature vulcanized silicone rubber and to an uncoated glass substrate. A novel suppression mechanism of the superhydrophobic coating is proposed which is driven by the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Normally, artificial hydrophobic surfaces typically involve chemical or textural modification, which has rough structure and low surface energy. , The morphology of the superhydrophobic Si M/N -K-PUa coating was studied by SEM, as shown in Figure g,h. It is clearly observed that the coating consists of microscale protrusions (Figure g) piled up with nanoscale particles (Figure h).…”
Section: Resultsmentioning
confidence: 99%
“…Normally, artificial hydrophobic surfaces typically involve chemical or textural modification, which has rough structure and low surface energy. , The morphology of the superhydrophobic Si M/N -K-PUa coating was studied by SEM, as shown in Figure g,h. It is clearly observed that the coating consists of microscale protrusions (Figure g) piled up with nanoscale particles (Figure h).…”
Section: Resultsmentioning
confidence: 99%
“…As an important parameter to evaluate insulation performance, flashover voltage is not only closely related to the surface charge but also directly related to the dissipation of surface charge and the distribution of surface trap level [24]. The trap distribution of the material could be obtained by measuring the surface potential decay according to the theory of homothermal surface potential decay [25]. Furthermore, the trap energy level distribution could be obtained according to the potential decay theory of the homothermal surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, their long-term exposure to environments with a high content of humidity such as seaward wind power station is prone to flashover due to high hydrophilicity, seriously constricting their applications [3]. Worse still, the wet flashover voltage is lower than the dry flashover one resulting in more hazards [4,5]. As the wet flashover voltage is dependent on surface physio-chemical properties, various methods have been explored for surface modification, such as physical polishing, direct fluorination, and low-temperature plasma material surface treatment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%